2017
DOI: 10.1007/s00493-016-3516-5
|View full text |Cite
|
Sign up to set email alerts
|

Connected Tree-Width

Abstract: The connected tree-width of a graph is the minimum width of a treedecomposition whose parts induce connected subgraphs. Long cycles are examples of graphs that have small tree-width but large connected tree-width. We show that a graph has small connected tree-width if and only if it has small tree-width and contains no long geodesic cycle.We further prove a connected analogue of the duality theorem for tree-width: a finite graph has small connected tree-width if and only if it has no bramble whose connected co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…A graph is roughly isometric to a tree if and only if it has bounded connected treewidth. We refer to [4] for an explanation of tree-width. In considering whether Theorem 1.1 is best possible, it is natural to ask whether we might be able to say that every graph of bounded tree-width has mixing time within a constant factor of its tree decomposition, without requiring the parts of the tree decomposition to be connected.…”
Section: Examplesmentioning
confidence: 99%
“…A graph is roughly isometric to a tree if and only if it has bounded connected treewidth. We refer to [4] for an explanation of tree-width. In considering whether Theorem 1.1 is best possible, it is natural to ask whether we might be able to say that every graph of bounded tree-width has mixing time within a constant factor of its tree decomposition, without requiring the parts of the tree decomposition to be connected.…”
Section: Examplesmentioning
confidence: 99%
“…We will now use ideas from [2] to bound the length of t-admissible paths in stable tree-decompositions. Together with Proposition 11, this will imply our main result.…”
Section: Bounding the Length Of Admissible Pathsmentioning
confidence: 99%
“…The connected tree-width ctw(G) is defined accordingly as the minimum width of a connected tree-decomposition of the graph G. Trivially, the connected tree-width of a graph is at least as large as its tree-width and, as Jegou and Terrioux [5] observed, long cycles are examples of graphs of small tree-width but large connected tree-width. Diestel and Müller [2] showed that, more generally, the existence of long geodesic cycles, that is, cycles in a graph G that contain a shortest path in G between any two of their vertices, raises the connected treewidth. Furthmore, they proved that these two obstructions to small connected tree-width, namely, large tree-width and long geodesic cycles, are essentially the only obstructions: Theorem 1 ([2, Theorem 1.1]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(see, for example, [6][7][8][9]14,[18][19][20][21][25][26][27][28][29][30][31][32][33][34][35]). x, y ∈ J(G) \ V(G), z ∈ J(G), …”
Section: Introductionmentioning
confidence: 99%